Draft Annual Plan 2011-12 Volume - III Development Planning, Economic Reforms and North Eastern Council Affairs Department Government of Sikkim - Planning Commission (Planning Commission, 2011)
In keeping with the emphasis of the State Government, the Department has been making every effort towards promotion of Art and Culture through its ongoing activities like workshops, kavi-sammelans, competition, fairs and festivals and Inter-State Cultural Exchange programmes. The preservation and conservation of old and traditional buildings, structures and places having historical and cultural importance, heritage sites are also given due priority. Similarly Archaeology, Archives and establishment of Museum is another important area that the Department has been concentrating on in the recent years. In addition to above, providing quality services to the people by way of upgradation of existing facilities and setting up of new libraries, particularly in the District, Sub-Divisional and Rural levels is another important responsibility the Department has been entrusted with.
Draft Annual Plan 2011-2012
Government of Sikkim